Temperature-dominated spatiotemporal variability in snow phenology on the Tibetan Plateau from 2002 to 2022 - Xu, Jiahui; Tang, Yao; Dong, Linxin; Wang, Shujie; Yu, Bailang; Wu, Jianping; Zheng, Zhaojun; Huang, Yan (The Cryosphere, 2024)
A detailed understanding of snow cover and its possible feedback on climate change on the Tibetan Plateau (TP) is of great importance. However, spatiotemporal variability in snow phenology (SP) and its influencing factors on the TP remain unclear. Based on the daily gap-free snow cover product (HMRFS-TP) with 500 m resolution, this study investigated the spatiotemporal variability in snow cover days (SCDs), snow onset date (SOD), and snow end date (SED) on the TP from 2002 to 2022. A structural equation model was used to quantify the direct and indirect effects of meteorological factors, geographical location, topography, and vegetation greenness on SP. The results indicate that the spatial distribution of SP on the TP was extremely uneven and exhibited temporal heterogeneity. SP showed vertical zonality influenced by elevation (longer SCD, earlier SOD, and later SED at higher elevations). A total of 4.62 % of the TP area had a significant decrease in SCDs, at a rate of −1.74 d yr−1. The SOD of 2.34 % of the TP area showed a significant delayed trend, at a rate of 2.90 d yr−1, while the SED of 1.52 % of the TP area had a significant advanced trend, at a rate of at −2.49 d yr−1. We also found a strong elevation dependence for the trend in SCDs ( R=-0.73). Air temperature, precipitation, wind speed, and shortwave radiation can directly affect SP as well as indirectly affect it by influencing the growth of vegetation, whereas the direct effect was much greater than the indirect effect. Geographical location (latitude and longitude) and topographic conditions (elevation and slope) indirectly affected SP by modulating meteorological conditions and the growth of vegetation. Vegetation primarily influences SP by intercepting the snow and regulating the balance of the solar radiation budget. Regarding the total effect, air temperature was found to be the dominant factor. This study contributes to the understanding of snow variation in response to global warming over the past 2 decades by providing a basis for predicting ...